PENGARUH KOMPOSISI MEDIA TANAM TERHADAP PERTUMBUHAN TANAMAN MINT (Mentha piperita L) PADA SISTEM WALL GARDEN - Al Adha, Senndi Akbar; Banjarnahor, Dina (Agros Journal of Agriculture Science, 2024)
Cultivating plants vertically (wall garden) can overcome the reduced availability of land, plants are planted on vertical panels or specially designed wall structures. This research aims to determine the growth, yield and quality of wall garden mint leaves grown using various mixtures of coconut fiber, husk charcoal and soil. The experiment was designed in a Complete Randomized Block Design with six treatments: T (soil), S (husk charcoal), K (coconut charcoal 1: soil 1), K1S2T1 (coconut fiber 1: charcoal husk 2: soil 1), K1S1T2 (coconut fiber 1: charcoal husk 1: soil 2). The composition of the planting media composition of coconut fiber, husk charcoal and soil in the wall garden system has a real influence on the growth of Mint Plants. The composition of the planting media composition of coconut fiber, husk charcoal and soil in the wall garden system had a real influence on the growth of Mint Plants in the K1S2T1 treatment.